An animation assisted training system for the Baseball cover, relay and cutoff play - Chang, C.-W.; Wu, Y.-P.; Lin, H.-W. (International Journal of Computer Science in Sport, 2012)
In baseball, the concepts of "cutoff", "relay", "cover" and "backup" are very important to the defensive aspect of the game. In this paper, we design and implement an animation assisted sport simulation system for general baseball "cover, relay and cutoff play" training. We treat the baseball and each player in the ball field as independent "objects" in that each object has its own objective. Each object in the field of play is subject to change once the ball is put into play by the pitcher. We follow a standard paradigm commonly used by the Taiwan national baseball team, and transfer the "cover, relay and cutoffplay" into several structured program rules that we refer to as the Decision Making Method. We also design two mechanisms, Fielding Zone Map and the Critical Time Points Interval, for our Decision Making Method. This simulation system allows users to choose what happens once the baseball is put into play, and provides four different scenarios. The system simulates the chosen play through the use of graphic animation while contintiously tracking the batted ball, batter, runner(s) ob base, number of outs, hit/out batting result. By using this simulation system, players, especially those at the amateur junior level, can improve greatly on all aspects of play in a short period of time. Also, by using this hierarchical design, our system can be easily adapted to many other sports by adjusting the variables.